ON PARANORMED I-CONVERGENT SEQUENCE SPACES OF INTERVAL NUMBERS
In this article we introduce and study the paranormed I-convergent sequence spaces C^I(A ,p), C ^I_0(A ,p), M^I_C (A ,p) and M^I_C_° (A ,p) on the sequence of interval numbers with the help of a bounded sequence p=(p_k) of strictly positive real numbers. We study some topological and algebraic properties and some inclusion relations on these spaces. , number=1, journal=Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), author=Khan, V. A. and Shafiq, M. and Ebadullah, K., year=2014, month=Apr., pages=103–114